Designing a Square Transposition Algorithm with a Spiral Schematic - hendrikpatiung (INOVTEK Polbeng - Seri Informatika, 2024)
This study aims to improve the security of the square transposition algorithm by implementing a spiral scheme as a more complex character position randomization method. Conventional square transposition algorithms have limitations in the variety of encryption patterns, which can reduce their effectiveness in protecting data from pattern-based cryptanalysis attacks. The spiral scheme is implemented by determining the order of placement and retrieval of characters in the transposition box in a circular manner, both from the outside to the inside and from the center point out, following a non-linear pattern. This method is designed to produce a low correlation between plaintext and ciphertext, thereby increasing the level of randomness in the encryption process. In this study, the effectiveness of the spiral scheme is evaluated through statistical analysis and cryptanalysis tests to measure the level of randomness and security of the encryption results compared to the linear transposition pattern. The test results show that the spiral scheme successfully increases the complexity of the ciphertext structure, making it more resistant to pattern analysis-based attacks. The implementation of this spiral scheme is expected to make a significant contribution to the development of more secure encryption techniques, especially for applications that require high protection against digital security threats. Thus, this method offers a stronger alternative in improving data security without requiring high computational complexity.